Epidemiology and Genetic Characterization of H3N8 Equine Influenza Virus Responsible for Clinical Disease in Algeria in 2011. Issue 6 (29th January 2014) - Laabassi, F.; Lecouturier, F.; Amelot, G.; Gaudaire, D.; Mamache, B.; Laugier, C.; Legrand, L.; Zientara, S.; Hans, A.
Summary An outbreak of equine influenza (EI) was reported in Algeria between May and July, 2011. The outbreak started in Tiaret, in west province of Algeria, and spread to the other parts of the country affecting almost 900 horses in many provinces. The population studied was composed of 325 horses from different groups of age. Clinical sign expression was age dependent. Indeed, a morbidity rate of 14.9% was observed in horses under 15 months old and a rate of 4.95% in horses over 8 years old. Interestingly, the morbidity rate raised sharply to reach 100% in horses aged between 18 months and 7 years. The virus (H3N8) was detected in nasopharyngeal swabs (n = 11) from non‐vaccinated horses using a qRT‐PCR targeting a portion of the gene encoding the matrix protein (M). The virus isolates were identified as H3N8 by sequencing the haemagglutinin (HA) and neuraminidase (NA) genes and were named from A/equine/Tiaret/1/2011 to A/equine/Tiaret/10/2011. Alignment of HA1 amino acid sequence confirmed that viruses belong to Clade 2 of the Florida sublineage in the American lineage. Moreover, they are closely related to A/equine/Yokohama/aq13/2010, A/equine/Eyragues/1/2010, A/equine/Bokel/2011 and A/equine/Lichtenfeld/2012. Our data indicate that this strain was also circulating in the European horse population in 2010, 2011 and 2012.